The Impact of Output Voltage Modulation Strategies on Power Losses in Inverter - Baskys, A.; Bleizgys, V.; Gobis, V. (Elektronika ir Elektrotechnika, 2009)
The technique and results of investigation of power losses in inverter obtained for case when proposed Space Vector Pulse Frequency Modulation (SVPFM) method with averaged pulse lengths is employed for forming of three-phase inverter output voltage are presented in the work. The obtained results were compared with the results gained for conventional SVPFM method. It is shown that employment of the suggested modification of the SVPFM method allows decreasing the power losses in inverter, which is used in frequency converter for AC induction motor control, as compared to the case when conventional SVPFM method is employed. It is stated that reduction of power losses is caused by introduction of the switch commutation algorithm, which enables to minimize the number of switching of inverter switches and avoid commutations at maximal current. Additional reduction of the power losses is achieved by use of averaged pulse lengths, which allow improving the initial part of voltage spectrum. Ill. 7, bibl. 7 (in English; summaries in English, Russian and Lithuanian).